تطور التكنولوجيا المالية ومساهمتها في تعزيز درجة الشمول المالي (Journal of Economics and Management Research, 2023)
هدفت هذه الدراسة إلى إبراز دور التكنولوجيا المالية في تعزيز درجة الشمول المالي وتطوير الخدمات المالية الرقمية، وتأتي أهمية هذه الدراسة كونها تتناول بالوصف والتحليل في تبيان مؤشرات الشمول المالي وعلاقتها بكفاءة الخدمات المالية. وقد أظهرت نتائج الدراسة أن الشمول المالي يساهم بشكل كبير في زيادة كفاءة وجودة الخدمات المالية والمصرفية الموجهة للفئات المهمشة وغير المشمولة ماليا على وجه الخصوص. كما خلصت أن الاقتصاديات التي تمكنت من تبني نظم حديثة ومطورة لتسوية العمليات المالية والمصرفية استطاعت زيادة مستويات تطبيق الشمول المالي، الأمر الذي مكنها من تقديم خدمات مالية ومصرفية متنوعة، وبتكلفة معقولة. This study aimed to focus on the role of financial technology in enhancing the degree of financial inclusion and developing digital financial services. The results of the study showed that financial inclusion contributes significantly to increasing the efficiency and quality of financial and banking services directed to marginalized and financially excluded groups in particular.It also concluded that the economies that were able to adopt modern and developed systems for settling financial and banking operations were able to increase the levels of application of financial inclusion, which enabled them to provide various financial and banking services, at a reasonable cost.